Waste-to-value: Synthesis of nano-aluminum oxide (nano-γ-Al2O3) from waste aluminum foils for efficient adsorption of methylene blue dye - Farah I.M.S. Sangor (16328955) (2023)
Waste-to-value strategy is a comprehensive strategy to reduce waste, add value and utilize resources sparingly and effectively for resource conservation. The current study aims to synthesize nano-aluminum oxide (nano-γ-Al2O3) from waste aluminum foils for efficient adsorption of methylene blue dye. Various parameters including the physiochemical analysis were investigated such as pH, initial dye concentration, and temperature to understand the adsorption process. The results revealed that the prepared nano-γ-Al2O3 appeared as a heterogeneous surface with deep cavities embedded within the structure. Such a feature is believed to facilitate the MB sorption onto nano-γ-Al2O3. Additionally, Fourier transform infrared spectra revealed the presence of various functional groups including Al-OH at 1628 cm-1 and O-H stretching at 3120 cm-1. Furthermore, the elemental composition confirmed the presence of Cl (34.61%), O (41%), and Al 24.36%). The BET analysis revealed that nano-γ-Al2O3 had a high surface area of 149.9 mg2 /g. The optimum pH at which maximum adsorption (70.96%) of MB took place was 6 at 25 °C. Desorption studies indicated 0.5 HCl was able to recover 37.5% MB from the spent nano-γ-Al2O3. Isotherm studies indicated that the MB adsorption onto the prepared nano-γ-Al2O3 was best Journal Pre-proof 2 explained using both Freundlich and Langmuir models. The maximum adsorption capacity (Q0 max) was 175.4 mg/g at 45°C. While accordingly to thermodynamic studies, the positive value for change in enthalpy (∆H°) indicated that the adsorption process was endothermic. While the negative value of Gibbs free energy (∆G°) indicated the reaction was feasible and spontaneous. Lastly, the positive value for change in entropy (∆S°) indicated the increase of the randomness of MB ion with the increase in temperature. Other Information Published in: Case Studies in Chemical and Environmental Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1016/j.cscee.2023.100394